Analysis of the computational resources of personal computers - Lopatkin, R.Yu.; Ivashchenko, V.A.; Ignatenko, S.N.; Kuprienko, V.V. (Інститут програмних систем НАН України, 2017)
The paper is dedicated to analysis of monitoring data of a characteristic research institute department. In the issue were detected regularities of PCs usage activity. Estimated free resources values that can be used for high performance scientific computing.